Magneto-dielectric properties of Ni0.25Cu0.25Zn0.50Fe2O4–BaTiO3 and its application as substrate of microstrip patch antennas - F. H. Ikhsan, F. H. Ikhsan; S. K. Yee, S. K. Yee; F. Esa, F. Esa; S. H. Dahlan, S. H. Dahlan; Vahid Nayyer, Vahid Nayyer; Adel Y. I. Ashyap, Adel Y. I. Ashyap (Springer, 2023)
This study explores the properties and potential of magneto-dielectric (MD) material Ni0.25Cu0.25Zn0.50Fe2O4–BaTiO3 as an antenna substrate for miniaturization and bandwidth enhancement. The MD material was synthesized using a solid-state method and different amounts of BaTiO3 (0, 5, 10, 15 and 20%) were added to improve its relative permittivity. Various investigations were carried out to analyze the crystallographic structure, microstructure, magnetic properties, permittivity, permeability, and losses of the samples at microwave frequencies. Results show that the MD composite with 5% BaTiO3 achieved a relative permittivity of 12.5 and a permeability of 2.9 at 0.7 GHz has enhanced the antenna’s operating bandwidth with a fractional bandwidth of 61.1% and directivity of 3.1 dBi. The MD material with 20% BaTiO3 showed potential as an antenna substrate for miniaturization, with a relative permittivity and permeability of 17.1 and 1.9, respectively. It also displayed better gain (- 8.9 dBi) and radiation efficiency (8%) compared to the antenna with 5% BaTiO3 (with a gain of - 14.4 dBi and radiation efficiency of 1.8%) as an antenna substrate. The findings of this study suggest that MD materials have significant potential as antenna substrates for miniaturization and bandwidth enhancement.